Estudo comparativo do acúmulo de massa seca e macronutrientes por plantas de Zea mays e Ipomoea hederifolia - Carvalho, L.b.; Bianco, S. [UNESP]; Bianco, M.s. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2014)
Two experiments were carried out under greenhouse conditions to study the accumulation and distribution of dry mass and macronutrients in maize and Ipomoea hederifolia. Plants of both species had grown, separately, in pots with sand substrate and irrigation with nutrient solution. Treatments were represented by the times of evaluation, realized in intervals of 14 days, starting at 21 days after emergence (DAE). A maize plant showed slight growth up to 30 DAE, when dry mass allocation was higher in roots and leaves (80%); while an I. hederifolia plant, up to 50 DAE, when the allocation of dry mass was higher in offshoots and leaves (79). Dry mass accumulation was almost five times greater in maize (134 g per plant) than in I. hederifolia (29 g per plant). The average values of N and K contents were greater in I. hederifolia. Maximum accumulations of macronutrients by maize were 1,431; 474; 1,832; 594; 340, and 143 mg per plant, while by I. hederifolia, 727; 52; 810; 350; 148, and 65 mg per plant, for N, P, K, Ca, Mg, and S, respectively. Mean accumulation rate of dry mass and macronutrients by maize plants was crescent up to 87 DAE, reaching the maximum value at 103 DAE; while being crescent up to 121 DAE by I. hederifolia plants, reaching the maximum value at 138 DAE. Thus, beyond the interference on harvesting process, a population of I. hederifolia also can compete with maize crop for nutrients.

Foram realizados dois experimentos em casa de vegetação com o objetivo de estudar o acúmulo e a distribuição de massa seca e macronutrientes em milho e Ipomoea hederifolia. Plantas das duas espécies foram cultivadas, separadamente, em vasos com substrato de areia e irrigação com solução nutritiva. Os tratamentos foram representados pelas épocas de amostragem, realizada a intervalos de 14 dias, iniciando 21 dias após a emergência (DAE). Uma planta de milho apresentou crescimento lento até 30 DAE, quando a alocação de massa seca foi maior em raízes e folhas (80%), e uma planta de I. hederifolia, até 50 DAE, quando a alocação de massa seca foi maior em ramos e folhas (79%). O acúmulo máximo de massa seca foi quase cinco vezes maior em milho (134 g por planta) comparado a I. hederifolia (29 g por planta). Em média, os teores de N e K foram maiores em plantas de I. hederifolia. Os acúmulos máximos de macronutrientes pelo milho foram de 1.431, 474, 1.832, 594, 340 e 143 mg por planta, e por I. hederifolia, de 727, 52, 810, 350, 148 e 65 mg por planta, para N, P, K, Ca, Mg e S, respectivamente. A taxa de acúmulo médio diário de massa seca e macronutrientes pelas plantas de milho foi crescente até 87 DAE, atingindo o máximo aos 103 DAE, enquanto para as plantas de I. hederifolia foi crescente até 121 DAE, atingindo o máximo aos 138 DAE. Assim, além da interferência na colheita, uma população de I. hederifolia também pode competir por nutrientes com a cultura do milho.
Comparative study of dry mass and macronutrients accumulation by Zea mays and Ipomoea hederifolia plants
Keywords: Maize; Morning-glory; competition for nutrients; weed interference; Milho; Corda-de-viola; competição por nutrientes; interferência de plantas daninhas